KUAT LENTUR MORTAR BERSERAT DENGAN MEMANFAATKAN LIMBAH BATA MERAH SEBAGAI SUBSTITUSI SEMEN - Kurniadi, Edi; Kurniawan, Agus; Himawan, Lava; Pratiwi, Nursifa Maulidini Rahma (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
The increase in infrastructure development activity in Indonesia has directly impacted the rising demand for construction materials, including red bricks. The red brick production process generates significant residue, where a single firing cycle can result in approximately 300 pieces of waste bricks, equivalent to 1.2% of total production. To provide an environmentally friendly solution, red brick waste is utilized as a partial substitute for cement in mortar production, along with the addition of roving fibers to enhance flexural strength performance. This study aims to examine the utilization of red brick waste as a cement substitute in mortar combined with the addition of roving fibers and its effect on flexural strength. The research employed a quantitative experimental method at the Building Materials Laboratory, Department of Civil Engineering, Vocational School, Universitas Gadjah Mada. The study utilized cement-to-sand mix ratios of 1:2, 1:3, 1:4, 1:5, and 1:6, with Portland cement substitution variations using red brick powder at 0%, 2.5%, 5%, 7.5%, and 10%. Roving fibers, cut to a length of 1 cm, were added at 2% by weight of cement. The specimens consisted of mortar beams with dimensions of 40x40x160 mm, tested at 28 days of age. The results indicated that for non-fiber mortar, the highest flexural strength was achieved at a 1:2 ratio with 0% substitution, reaching 4.62 MPa. The maximum flexural strength was recorded at a 1:2 ratio with 2.5% red brick waste substitution and 2% roving fibers, measuring 5.13 MPa. Significantly, the addition of roving fibers improved mortar performance. A 20.7% increase in flexural strength was observed at the 1:2 ratio with 2% roving fibers and 2.5% cement substitution when compared to the mortar with 2.5% cement substitution without fibers, demonstrating the effectiveness of red brick waste and roving fibers as sustainable alternative materials.